Molecular Identification of Mycobacterium Species of Public Health and Veterinary Importance from Cattle in the South State of México - Adrian Zaragoza Bastida; Nallely Rivero Pérez; Benjamín Valladares Carranza; Keila Isaac-Olivé; Pablo Moreno Pérez; Horacio Sandoval Trujillo; Ninfa Ramírez Durán (Canadian Journal of Infectious Diseases and Medical Microbiology)
Mycobacterium genus causes a variety of zoonotic diseases. The best known example is the zoonotic tuberculosis due to M. bovis. Much less is known about “nontuberculous mycobacteria (NTM),” which are also associated with infections in humans. The Mexican standard NOM-ZOO-031-1995 regulates the presence of M. bovis in cattle; however, no regulation exists for the NTM species. The objective of this study was to isolate and identify nontuberculous mycobacteria species from cattle of local herds in the south region of the State of Mexico through the identification and detection of the 100 bp molecular marker in the 23S rRNA gene with subsequent sequencing of the 16S rRNA gene. Milk samples (35) and nasal exudate samples (68) were collected. From the 108 strains isolated, 39 were selected for identification. Thirteen strains isolated from nasal exudates amplified the 100 bp molecular marker and were identified as M. neoaurum (six strains), M. parafortuitum (four strains), M. moriokaense (two strains), and M. confluentis (one strain). Except M. parafortuitum, the other species identified are of public health and veterinary concern because they are pathogenic to humans, especially those with underlying medical conditions.